Surgical management of pancreatic neoplasms in children: a single-institution experience over 15 years - Ho, In Geol; Ihn, Kyong; Le, Sung Min; Shin, Soyong; Han, Seok Joo (Frontiers in Pediatrics, 2024)
Introduction: Pancreatic neoplasms are rare among children and very few studies have reported on surgical outcomes for pediatric pancreatic neoplasms. Therefore, we aimed to describe patient and tumor characteristics and report on the surgical outcomes of pediatric pancreatic neoplasm. Methods: In this retrospective single-center study, we reviewed and analyzed the data of patients who underwent surgery for pediatric pancreatic neoplasms at Severance Children's Hospital between January 2007 and December 2022. Clinical data including demographics, surgical procedures, and postoperative and long-term outcomes were evaluated. Results: A total of 28 patients underwent surgical treatment for pancreatic neoplasms with a median age of 11.7 years (range: 0.4-17.8). The most common histological diagnosis among benign tumors was solid pseudopapillary neoplasm (SPN), which occurred in 20 patients (71.4%). This was followed by a mucinous cyst, nesidioblastosis, pseudocyst, duplication cyst, and benign cyst, each occurring in one patient (3.5%). Regarding malignant tumors, pancreatoblastoma, solid pseudopapillary carcinoma, and malignant pheochromocytoma were noted in one patient each (3.5%). Tumor locations included the head in 4 patients (14.2%), the body in 7 (25%), and the tail in 16 (57.1%), and was diffuse in 1 (3.5%). The most common surgical resection range was distal pancreatectomy, found in 22 patients (78.5%), followed by pylorus-preserving pancreaticoduodenectomy, found in 2 (7.2%); duodenum-preserving pancreatic resection, central pancreatectomy, tumor enucleation, and near-total pancreatectomy were performed in one patient each (3.5%). Overall, 4 patients developed grade B or C postoperative pancreatic fistulas, and 1 experienced postoperative mortality due to uncontrollable bleeding. The mean follow-up period was 6.1 years (range: 1-15.6 years), during which no significant impact on growth after surgery was detected. Among the 20 patients with SPN, tumor rupture occurred in 4 (20%), among whom 2 experienced tumor recurrences. Conclusions: Histological diagnosis of benign tumors was predominant in this case series and various extents of surgical resection were performed. Surgical treatment for pediatric pancreatic neoplasms appears to be safe and effective. However, considering the long-term prognosis of these patients, it is essential to determine the appropriate extent of surgical resection based on the location of the tumor.